Innovative geoelectric methods: multi-year experience of application for the practical problems of near-surface geophysics operative solution - S. P. Levashov; N. A. Yakymchuk; I. N. Korchagin (Геофизический журнал, 2018)
The results of practical application of mobile geophysical methods for the operational detection and mapping of underground water streams and aquifers at several construction sites in Kiev are presented and analyzed. Geoelectric methods of the forming a short-pulsed electromagnetic field (FSPEF(SCIP)) and vertical electric-resonance sounding (VERS); as well as the method of georadar sounding; were used in the studies. The mobile methods of SCIP and VERS were developed on the principles of a “sub-stance” paradigm of geophysical research; within which a “direct” search for a specific physical substance is carried out: gas; oil; gas hydrates; water; ore minerals and rocks (gold; platinum; silver; zinc; uranium; diamonds; kimberlites; etc.). The effectiveness of geophysical methods; based on the principles of this paradigm; is significantly higher than traditional ones. The results of the performed works showed that the survey by SCIP method within area allows to detect and map quickly the zones of rocks moistening; underground water streams of natural and technogenic origin and aquifers. The VERS sounding with high accuracy determines the depth and thickness of water-saturated horizons in the cross-section. Field work of this nature is carried out quickly and enough operatively. Specific research materials of a survey nature demonstrate sufficiently reasonably the destructive effect of underground water flows on various objects (including those under construction) of a modern city. They also point to the objective need to identify and map destructive underground flows even at the stages of engineering and geological surveys for the construction of engineering structures; buildings and facilities for various purposes. Ignoring this need in many cases leads to significant time and material costs. The presented results; as well as previous work at various construction sites; show that the mobile complex used allows efficiently and effectively a) to allocate zones of increased soil moistening; b) determine the directions and ways of migration of filtration water streams of natural and technogenic origin; c) determine the depths and thickness of the watered rock horizons; d) determine on the area the thickness of loose deposits; the roof of the gruss and the granite basement; e) identify and trace the tectonic fractures within the site of work; etc. The individual methods included in this complex can also be used for monitoring observations at construction sites in order to determine the impact of the facilities under construction on engineering and geological conditions; both in the construction sites and in the surrounding areas. The practical application of mobile technology during the engineering and geological research conducting for the construction of large engineering facilities can bring significant economic benefits due to a significant reduction in the duration of survey work and a significant reduction in volumes of drilling.